EFEKTIVITAS PENERAPAN METODE BERMAIN CHOOSE NUMBER DALAM PEMBELAJARAN MATEMATIKA - Fikri Alfiani; Muhajir; Mila Karmila (Jurnal Penalaran dan Riset Matematika, 2024)
This type of research is pre-experimental research involving one class. The aim of this research is to determine learning outcomes by applying the Choose Number playing method in mathematics learning in class IV at SD Negeri 7 Tarowang. The experimental units in this research were 28 class IV students. The research was carried out over 3 meetings. The research results showed that from 28 students learning using conventional methods, there were 24 students in the incomplete category with a percentage of 85%, and 4 students in the complete category with a percentage of 15%. Classically it has not been fulfilled because the average score obtained was 52.10, whereas in learning using teaching aids there were 7 students who were in the incomplete category with a percentage of 25%, and 21 students who were in the completed category with a percentage of 75%. This means that classical learning completeness is fulfilled with an average score of 82.07 which has achieved the expected KKM of 70. Based on the results of this research, it can be concluded that the Choose Number playing method in class IV mathematics learning at SD Negeri 7 Tarowang is effectively implemented.